Clinical and microbiological outcomes, by causative pathogen, in the ASPECT-NP randomized, controlled, Phase 3 trial comparing ceftolozane/tazobactam and meropenem for treatment of hospital-acquired/ventilator-associated bacterial pneumonia. (12th January 2022) - Martin-Loeches, Ignacio; Timsit, Jean-François; Kollef, Marin H.; Wunderink, Richard G.; Shime, Nobuaki; Nováček, Martin; Kivistik, Ülo; Réa-Neto, Álvaro; Bruno, Christopher J.; Huntington, Jennifer A.; Lin, Gina; Jensen, Erin H.; et al.
Abstract: Objectives: In the ASPECT-NP trial, ceftolozane/tazobactam was non-inferior to meropenem for treating nosocomial pneumonia; efficacy outcomes by causative pathogen were to be evaluated. Methods: Mechanically ventilated participants with hospital-acquired/ventilator-associated bacterial pneumonia were randomized to 3 g ceftolozane/tazobactam (2 g ceftolozane/1 g tazobactam) q8h or 1 g meropenem q8h. Lower respiratory tract (LRT) cultures were obtained ≤36 h before first dose; pathogen identification and susceptibility were confirmed at a central laboratory. Prospective secondary per-pathogen endpoints included 28 day all-cause mortality (ACM), and clinical and microbiological response at test of cure (7–14 days after the end of therapy) in the microbiological ITT (mITT) population. Results: The mITT population comprised 511 participants (264 ceftolozane/tazobactam, 247 meropenem). Baseline LRT pathogens included Klebsiella pneumoniae (34.6%), Pseudomonas aeruginosa (25.0%) and Escherichia coli (18.2%). Among baseline Enterobacterales isolates, 171/456 (37.5%) were ESBL positive. For Gram-negative baseline LRT pathogens, susceptibility rates were 87.0% for ceftolozane/tazobactam and 93.3% for meropenem. For Gram-negative pathogens, 28 day ACM [52/259 (20.1%) and 62/240 (25.8%)], clinical cure rates [157/259 (60.6%) and 137/240 (57.1%)] and microbiological eradication rates [189/259 (73.0%) and 163/240 (67.9%)] were comparable with ceftolozane/tazobactam and meropenem, respectively. Per-pathogen microbiological eradication for Enterobacterales [145/195 (74.4%) and 129/185 (69.7%); 95% CI: −4.37 to 13.58], ESBL-producing Enterobacterales [56/84 (66.7%) and 52/73 (71.2%); 95% CI: −18.56 to 9.93] and P. aeruginosa [47/63 (74.6%) and 41/65 (63.1%); 95% CI: −4.51 to 19.38], respectively, were also comparable. Conclusions: In mechanically ventilated participants with nosocomial pneumonia owing to Gram-negative pathogens, ceftolozane/tazobactam was comparable with meropenem for per-pathogen 28 day ACM and clinical and microbiological response.